2017
DOI: 10.1016/j.pharep.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of kaempferol inhibits bone loss in rat model of ovariectomy-induced osteopenia

Abstract: Kaempferol has a beneficial influence on estrogen-deficiency-induced disturbances of bone structure in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…From the in vivo assessment of bone microarchitecture, the present study verified that the bone mass parameters (BMD, BV/TV, Tb.N and Tb.Th) were significantly elevated, and the parameters of osteoporosis (SMI and Tb.Sp) reduced in OVX rats treated with Kae compared with OVX group rats. These changes in bone morphology induced by Kae in OVX rats are similar to those found in previously published research (26,27). However, the concentration of Kae used in the in vivo experiment of the present study was higher than that of previous studies (26,27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…From the in vivo assessment of bone microarchitecture, the present study verified that the bone mass parameters (BMD, BV/TV, Tb.N and Tb.Th) were significantly elevated, and the parameters of osteoporosis (SMI and Tb.Sp) reduced in OVX rats treated with Kae compared with OVX group rats. These changes in bone morphology induced by Kae in OVX rats are similar to those found in previously published research (26,27). However, the concentration of Kae used in the in vivo experiment of the present study was higher than that of previous studies (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…These changes in bone morphology induced by Kae in OVX rats are similar to those found in previously published research (26,27). However, the concentration of Kae used in the in vivo experiment of the present study was higher than that of previous studies (26,27). The similarity of the results may be associated with differences in delivery time or the vehicle solution used in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study demonstrated that oral administration of kaempferol (5 mg/kg) for 8 weeks increased femoral bone mineral density (BMD) and Young’s modulus of elasticity but decreased osteocalcin (OCN) and RANKL in OVX rats. Histologically, the OVX rats receiving kaempferol had higher bone volume/total volume (BV/TV), trabecular bone area (B.Ar), trabecular bone perimeter (B.Pm) and bone surface/total volume (BS/TV) relative to the negative control animals 22. Kaempferitrin, another name for kaempferol-3,7-dirhamnoside, at the dose of 8 or 16 mg/kg had been shown to increase BMD, bone mineral content (BMC), tissue mineral content, tissue mineral density, bone volume fraction, trabecular number (Tb.N), connectivity density (Conn.D) and decrease trabecular separation (Tb.Sp) in the OVX rats.…”
Section: In Vivo Studies On the Effects Of Kaempferol On Bonementioning
confidence: 99%
“…Kaempferitrin also influenced the levels of bone formation and resorption markers, whereby a higher level of ALP, as well as lower levels of cathepsin K and tartrate-resistant acid phosphatase (TRAP), were observed after the treatment 23Table 1In Vivo Studies On The Bone-Protecting Properties Of KaempferolAnimal StrainExperimental GroupsOutcomesReferenceNewborn Sprague–Dawley ratsControlKaempferol (5 μM, injected into the top of the periosteum of the parietal bone)Compared to normal group, treatment with kaempferol: ↑ BSP, OSX and Runx-2↑ bone area and number of osteoblasts↑ osteoblast differentiationYang et al20 (2010)Female Sprague–Dawley rats (n=10/group)ShamOVXOVX + kaempferol (5 mg/kg, oral)Compared to OVX group, treatment with kaempferol: ↑ BMD in total femur, femoral neck, proximal tibia, total vertebra and L3 vertebra↑ compressive energy for L3 vertebra and ↓ ALP↑ mineralization and ↓ adipogenesis in bone marrow cellsTrivedi et al21 (2008)Female Wistar rats (n=8/group)ShamOVXOVX + kaempferol (5 mg/kg, oral)Compared to OVX group, treatment with kaempferol: ↑ BMD and Young’s modulus↓ OCN and RANKL↑ BV/TV, B.Ar, B.Pm and BS/TVNowak et al22 (2017)Female Sprague–Dawley rats (n=8/group)ShamOVXOVX + estradiol valerate (1 mg/kg, oral)OVX + kaempferitrin (8 mg/kg, oral)OVX + kaempferitrin (16 mg/kg, oral)Compared to OVX group, treatment with kaempferitrin: ↑ BMD, BMC, tissue mineral content, tissue mineral density, bone volume fraction, Tb.N, Conn.D and ↓ Tb.Sp↑ ALP, ↓ cathepsin K and TRAPMa et al23 (2015)Female Sprague–Dawley rats (n=10/group)NormalMethylprednisolone (5 mg/kg, s.c.)Methylprednisolone (5 mg/kg, s.c.) + kaempferol (5 mg/kg, oral)Methylprednisolone (5 mg/kg, s.c.) + human 1–34 PTH (5 μg/kg, 5 times/week, s.c.)Compared to methylprednisolone-treated group, treatment with kaempferol: ↑ BV/TV, BS/TV, Tb.N, Conn.D, ↓ Tb.Sp and SMI of proximal tibial metaphyseal region↑ Cs.Th, MMI, B.Pm and T.Pm of tibial diaphyseal region↑ BMD of femur and tibia↑ BFR, MAR and MS of femur diaphysis↑ energy to failure and stiffness of femur diaphysis↑ P1NP and ↓ CTX-1 in serum↑ ...…”
Section: In Vivo Studies On the Effects Of Kaempferol On Bonementioning
confidence: 99%
“…Quercetin can also directly or indirectly down-regulate the expression of RANKL, inhibit osteoclast differentiation, reduce bone resorption, and stimulate osteoblast activity through estrogen signaling pathway and ERK signaling pathway [31]. Kaempferol has also been shown to have bone protective effects on ovariectomized rats [32], possibly through estrogen receptor, MAPK, NF-κB and other signaling pathways [33]. Luteolin can prevent bone loss after osteoporosis by inhibiting osteoclast differentiation.…”
Section: Key Active Ingredient Of Zytlf For Anti-pmopmentioning
confidence: 99%